Reliability and maintenance modeling with optimization : advances and applications - Kimura, Mitsutaka (Advanced research in reliability and system assurance engineering., 2023)
"Reliability and maintenance modeling with optimization is the most fundamental and interdisciplinary research area and it can be applied to every technical and management field. This monograph provides the most recent advances and achievements in reliability and maintenance. The book discusses replacement, repair, inspection, estimation, and statistical tests along with accelerated life testing. It explores warranty analysis manufacturing and also service reliability"--